The holy bible Douay-Rheims Version, Challoner revision, the Old and New Testaments - Challoner, Richard, 1691-1781 ([Auckland] : Floating Press, 2011)
Perhaps the single most important and influential text ever published, the Holy Bible is a masterwork of spiritual writing. Whether you're a committed Christian seeking inspiration or an intellectually curious reader interested in the cultural value of the Bible, this easy-to-read version of the Good Book is sure to meet your needs.
The Second Epistle of St. Paul to TimothyThe Epistle of St. Paul to Titus -- The Epistle of St. Paul to Philemon -- The Epistle of St. Paul to the Hebrews -- The Catholic Epistle of St. James the Apostle -- The First Epistle of St. Peter the Apostle -- The Second Epistle of St. Peter the Apostle -- The First Epistle of St. John the Apostle -- The Second Epistle of St. John the Apostle -- The Third Epistle of St. John the Apostle -- The Catholic Epistle of St. Jude -- The Apocalypse of St. John the Apostle.
Archived by the National Library of New Zealand in PDF (4260 pages).
"From a 1752 edition"--Page 2 of PDF.
Hypertext links contained in the archived instances of this title are non-functional.
Keywords: Bible; Bible; Sacred books; BIBLES -- Multiple Translations -- Children; BIBLES -- Multiple Translations -- Devotional; BIBLES -- Multiple Translations -- Reference; BIBLES -- Multiple Translations -- Study; BIBLES -- Multiple Translations -- Text; BIBLES -- Multiple Translations -- Youth & Teen; Electronic books